Defining Legal Boundaries to Combat Unfair Competition: An Analysis of Eu Law and International Practice - Abdurakhimov Abdumalik Rakhmonkulovich (International Journal of Law And Criminology, 2025)
This article examines the issue of combating unfair competition within both international and national legal frameworks. The author explores the scope and limitations of exclusive rights in relation to intellectual property, particularly focusing on the newly introduced neighboring rights of press publishers as outlined in Directive (EU) 2019/790. Using France’s legal and judicial response to Google’s behavior as a case study, the paper analyzes how competition authorities have intervened to protect press publishers from abuse of dominant market position by digital platforms. The article also considers the lack of clear legal boundaries in digital environments and the importance of adapting national antitrust policies to reflect evolving international standards. In doing so, it proposes a framework for legal harmonization and balanced rights enforcement in the digital economy.